Frequency of Zygomatic Complex Fracture in Patients Presenting to Ayub Teaching Hospital: Frequency of Zygomatic Complex Fracture - Mumtaz, Sundus; Khan, Tanveer Ahmed; Rasheed, Maria; Waqas, Muhammad Abi; Gul, Ghazanfar; Ishaque, Palwasha (Pakistan Journal of Health Sciences, 2024)
Zygomatic complex fractures are a prevalent type of facial injury. It often results from road traffic accidents (RTA). It poses significant clinical challenges. Objective: To find out the frequency of zygomatic complex fractures among patients introduced at the Ayub Teaching Hospital. Methods: This cross-sectional study was carried out in the Department of Oral and Maxillofacial Surgery at Ayub Teaching Hospital, Abbottabad, Pakistan after approval from IRB (Institutional Review Board) of the Ayub Teaching Hospital Abbottabad, (IRB-F5/Dent/AMC&ATH) from September 1, 2019, to March 1, 2020. A total of 146 patients, including both genders and revealing oral and maxillofacial injury, were essential parts of the research. Before performing meticulous intra and extra-oral clinical examinations and computed tomography (CT) scans in the Department of Radiology to diagnose zygomatic complex fractures. Results: Out of the total number of 146 patients, 33.6% had ZMC fractures. The study involved patients aged 18-60 years. This is consistent with an average age of 31.993 ± 8.00 years and a mean weight of 74.664 ± 9.26 kg. Male patients represented 74.7% of cases and female comprised 25.3%. The primary causes of fractures were road traffic accidents, falls, and sports injuries. Conclusions: The research concluded that zygomatic complex fractures occurred due to road traffic accidents (RTA), which are more common in this region. Thus, the examination highlights the basic requirement for procedures to alleviate street mishaps to abridge such terrible facial injuries.